2015
DOI: 10.4103/0300-1652.169707
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and antidiabetic activities of watermelon (Citrullus lanatus) juice on oxidative stress in alloxan-induced diabetic male Wistar albino rats

Abstract: Background:The nutritional and medicinal importance of watermelon has been emphasized and its diseases preventive and curative power must be evaluated. Hence, this study was designed to evaluate the antioxidative and antidiabetic potentials of watermelon.Materials and Methods:The in vivo assay was carried out on 15 male albino rats which were divided into groups of three stages. In stage I, all animals received normal feeds and water for 1-week after, which five animals were selected and sacrificed for biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…In this study, administering 0.5 g/kg L‐citrulline to high‐fat diet fed Sprague Dawley (SD) rats for 11 weeks could significantly decrease insulin and homeostatic model assessment of insulin resistance (HOMA‐IR) . In a study by Oseni et al , feeding crude extracts of watermelon to diabetic Wistar albino rats for 1 week resulted in a significant decrease of glucose . Also, Okechukwu et al , reported a significant decrease in glucose level after 4 weeks of feeding extract of watermelon rind ( Citrullus lanatus ) mixed with guinea feed in a ratio of 3:1 to diabetic rats .…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…In this study, administering 0.5 g/kg L‐citrulline to high‐fat diet fed Sprague Dawley (SD) rats for 11 weeks could significantly decrease insulin and homeostatic model assessment of insulin resistance (HOMA‐IR) . In a study by Oseni et al , feeding crude extracts of watermelon to diabetic Wistar albino rats for 1 week resulted in a significant decrease of glucose . Also, Okechukwu et al , reported a significant decrease in glucose level after 4 weeks of feeding extract of watermelon rind ( Citrullus lanatus ) mixed with guinea feed in a ratio of 3:1 to diabetic rats .…”
Section: Resultsmentioning
confidence: 79%
“…The effects of watermelon extract on oxidative stress have been reported in one study. Oseni et al reported a significant decrease in malondialdehyde (MDA) and a significant increase in glutathione, glutathione peroxidase (GPx) and superoxide dismutase (SOD) percentage activity and a slight increase in catalase (CAT) activity after feeding diabetic Wistar rats with crude extracts of watermelon for one week …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations